THE SNAKE AND THE ROUNDABOUT: ETHICAL PARTICULARISM AND THE PATTERNS OF NORMATIVE INDUCTION A SERPENTE E A ROTUNDA: PARTICULARISMO ÉTICO E OS PADRÕES DA INDUÇÃO NORMATIVA - Kellogg (George Washington University), Frederic R. (Duc In Altum - Cadernos de Direito, 2017)
Using two examples of ethical choice, Philippa Foot’s snake and the traffic roundabout, this paper offers an account of normative induction that characterizes particularism and generalism as stages of normative inquiry, rather than rival accounts of moral knowledge and motivation. Ethical particularism holds that the evaluative cannot be “cashed out” in propositional form, and that it is descriptively “shapeless.” Drawing on examples from law, this paper claims that, while individual normative inquiry may be viewed as encountering a shapeless particularist context of seem-ingly unlimited nonmoral properties, normativity is driven by repe-tition of similar situations toward shared practices and descriptive predication. Rather than retention of epistemic status by defeated reasons, this illustrates retirement of relevant properties and ac-companying reasons, transformation of the reasons environment, and a pluralist normative ontology.